The Influence of Principal’s Leadership Style and Teacher’s Motivation on Teacher’s Performance at SMK Negeri Kayuagung Sub-District - Marlianti, Yenni; Widayatsih, Tri; Fahmi, Muhammad (Journal of Social Work and Science Education, 2023)
Teacher performance is an important element in achieving the goals of educational institutions. Therefore, educational institutions must be able to maximize the factors that can affect teacher performance, which are the principal’s leadership style and teacher motivation. This study aims to analyze the effect of the principal’s leadership style and teacher motivation on teacher performance in SMK Negeri throughout the Kayuagung District. This type of research is quantitative research. Data collection tool using a questionnaire. Data analysis using multiple regression tests. The results of the study stated that there was an influence of the principal’s leadership style and teacher motivation on the performance of teachers in State Vocational Schools throughout the Kayuagung District. To improve their performance, teachers must have high motivation and support from the leadership of the principal who can keep the teacher’s motivation always in good condition so that the teaching and learning process can run effectively.